Episodes of Student Vandalism in Higher Education Institutions in South Africa - Mzenzi, Athiphila; Kang'ethe, Simon Murote (Research in Social Sciences and Technology, 2025)
The South African higher education sector is annually buffeted with student unrest, ensuing costly vandalism of institutional property and jeopardy of academic progress. This paper explores episodes of vandalism in higher education institutions in South Africa. The literature review is utilised as a qualitative sub-methodology. 47 journal articles and one book chapter were accessed using data engines such as EBSCOhost, the Web of Science, Scopus, ProQuest and Google Scholar to analyse and synthesise thematic findings. The study established the following findings: Student indiscipline emanating from their social backgrounds, destruction of property, reputational deficits, and litigation consequences to students. The paper recommends that the next academic studies focus on determining the global, regional and South African statistical prevalence of student vandalism in higher education institutions.